Plasma Trimethylamine-N-Oxide Is an Independent Predictor of Long-Term Cardiovascular Mortality in Patients Undergoing Percutaneous Coronary Intervention for Acute Coronary Syndrome - Eyileten, Ceren; Jarosz-Popek, Joanna; Jakubik, Daniel; Gasecka, Aleksandra; Wolska, Marta; Ufnal, Marcin; Postula, Marek; Toma, Aurel; Lang, Irene M.; Siller-Matula, Jolanta M. (Frontiers in Cardiovascular Medicine, 2021)
To investigate the association of liver metabolite trimethylamine N-oxide (TMAO) with cardiovascular disease (CV)-related and all-cause mortality in patients with acute coronary syndrome (ACS) who underwent percutaneous coronary intervention. Our prospective observational study enrolled 292 patients with ACS. Plasma concentrations of TMAO were measured during the hospitalization for ACS. Observation period lasted 7 years in median. Adjusted Cox-regression analysis was used for prediction of mortality. ROC curve analysis revealed that increasing concentrations of TMAO levels assessed at the time point of ACS significantly predicted the risk of CV mortality (c-index=0.78, p<0.001). The cut-off value of >4 μmol/L, labeled as high TMAO level (23% of study population), provided the greatest sum of sensitivity (85%) and specificity (80%) for the prediction of CV mortality and was associated with a positive predictive value of 16% and a negative predictive value of 99%. A multivariate Cox regression model revealed that high TMAO level was a strong and independent predictor of CV death (HR=11.62, 95% CI: 2.26-59.67; p=0.003). High TMAO levels as compared with low TMAO levels were associated with the highest risk of CV death in a subpopulation of patients with diabetes mellitus (27.3% vs 2.6%; p=0.004). Although increasing TMAO levels were also significantly associated with all-cause mortality, their estimates for diagnostic accuracy were low. High TMAO level is a strong and independent predictor of long-term CV mortality among patients presenting with ACS. TMAO concentration of 4 μmol/L may be a cut-off value for prognosis of ACS patients.